2020
DOI: 10.1016/j.psj.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-catenin signaling pathway is involved in regulating feather growth of embryonic chicks

Abstract: Avian feathers have robust growth and regeneration capability and serve as a useful model for decoding hair morphogenesis and other developmental studies. However, the molecular signaling involved in regulating the development of feather follicles is unclear. The purpose of this study was to investigate the role of the Wnt/β-catenin pathway in regulating feather morphogenesis in embryonic chicks through in ovo injection of different doses of Dickkopf-1 (DKK1, a specific inhibitor of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Proteins were isolated from jejunum samples and analyzed as described previously ( Xie et al., 2020 ). Total protein was extracted from the intestinal tissues using radioimmunoprecipitation assay lysis buffer, and the protein concentration in the homogenates was determined using the BCA protein assay kit (Thermo Fisher Scientific, Rockford, Illinois, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were isolated from jejunum samples and analyzed as described previously ( Xie et al., 2020 ). Total protein was extracted from the intestinal tissues using radioimmunoprecipitation assay lysis buffer, and the protein concentration in the homogenates was determined using the BCA protein assay kit (Thermo Fisher Scientific, Rockford, Illinois, USA).…”
Section: Methodsmentioning
confidence: 99%
“… Zhou et al (2018) reported that activation of the Wnt/β-catenin signaling pathway regulates hair growth and cycle transition in mouse model. While injecting Dickkopf-related protein 1 ( DKK1 ), a secreted antagonist of the canonical Wnt signaling pathway, into chick embryos at E9 inhibits feather follicles development and feather growth via inhibiting the Wnt/β-catenin signaling pathway ( Xie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The yolk sac is an extra-embryonic component surrounding the yolk and responses for nutrient absorption, digestion and transportation during incubation of the avian embryo, as well as during early term of mammalian embryonic development ( Yadgary et al, 2014 ). Yolk sac plays an important role during embryonic development, yolk sac feeding, or injection is exhibiting positive effects on embryonic development modulation ( Slawinska et al 2016 ; Chen et al 2020 ; Xie et al 2020 ). Previous studies have illustrated that CHIR-99021 has ability to influence morphogenesis and development of various organs and tissues including fat ( Chen et al, 2018 ), liver ( Russell and Monga, 2018 ; Perugorria et al, 2019 ), tooth ( Järvinen et al, 2018 ), lung ( Stewart 2014 ), skeletal muscle ( Girardi and Le Grand, 2018 ), and stomach ( Barker et al, 2010 ) via regulating the Wnt signaling pathway, besides, transcription factors and enzymes have been identified as key mediators participating in the processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins were isolated from jejunum samples and analyzed as described previously ( Xie et al., 2020 ). The expression levels were quantified using ImageJ software (version 1.8.0 112, National Institute of Health, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%